2004
DOI: 10.2134/jeq2004.1240
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a δ15N Isotopic Method to Indicate Anthropogenic Eutrophication in Aquatic Ecosystems

Abstract: Increased anthropogenic delivery of nutrients to water bodies, both freshwater and estuarine, has caused detrimental changes in habitat, food web structure, and nutrient cycling. Nitrogen-stable isotopes may be suitable indicators of such increased nutrient delivery. In this study, we looked at the differences in response of macrophyte delta15N values to anthropogenic N across different taxonomic groups and geographic regions to test a stable isotopic method for detecting anthropogenic impacts. Macrophyte delt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
125
1
7

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 235 publications
(146 citation statements)
references
References 45 publications
13
125
1
7
Order By: Relevance
“…It has been noted that elevated δ 15 N values of PN susp in the New Caledonian lagoon may be influenced by island runoff, and particularly untreated sewage which typically has a δ 15 N values of 5 to 20 ‰ (Cole et al, 2004). Although the VAHINE site was located 28 km from the coast, and strongly influenced by inflowing oceanic water, the elevated δ 15 N values of PN susp , despite a high contribution of N 2 fixation, indicated that the δ 15 N values of PN susp were influenced by landderived inputs (Knapp et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that elevated δ 15 N values of PN susp in the New Caledonian lagoon may be influenced by island runoff, and particularly untreated sewage which typically has a δ 15 N values of 5 to 20 ‰ (Cole et al, 2004). Although the VAHINE site was located 28 km from the coast, and strongly influenced by inflowing oceanic water, the elevated δ 15 N values of PN susp , despite a high contribution of N 2 fixation, indicated that the δ 15 N values of PN susp were influenced by landderived inputs (Knapp et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the assessment of anthropogenic pollution in aquatic ecosystems with the ı 15 N isotopic method has been widely tested on organisms of different trophic levels as biological indicators in aquatic ecosystems, including plants, invertebrates, and fishes (Lake et al, 2001;Cole et al, 2004;Schlacher et al, 2005;Xu et al, 2007). In addition the elevated ı 15 N signatures in aquatic biota are known to be correlated with increased exposure to human septic or sewage waste (Cole et Oligochaete Chironomus …”
Section: Discussionmentioning
confidence: 99%
“…Scientists tested common primary producers, such as phytoplanktons, microalgae, and macrophytes, which served as bioindicators of anthropogenic nitrogen input in a variety of aquatic ecosystems (e.g. Cole et al, 2004;Benson et al, 2008). For instance, the increase in ı 15 N values of periphytons is related to nutrient enrichment, reflecting the increase in relative contribution of sewage in river systems (Toda et al, 2002;Bergfur et al, 2009).…”
Section: ı 15 N Of Primary Producers As An Bioindicatormentioning
confidence: 99%
“…The use of nitrogen (N) isotopes to quantitatively model trophic structure and to identify nutrient pollution sources is proving increasingly valuable (Cabana and Rasmussen 1996;McKinney et al 2002;Post 2002;Cole et al 2004;Vander Zanden et al 2005;Gustafson et al 2007;Bergfur et al 2009;Wen et al 2010;Xu and Zhang 2012). Isotopic signatures of consumers are affected by the isotopic composition of the nutrients and organic compounds forming the base of their food webs (Cabana and Rasmussen 1996;Post 2002).…”
Section: Introductionmentioning
confidence: 99%